Facile fabrication of nanotubular heterostructure for enhanced photoelectrochemical performance - Han, Hyun Soo; Park, Woosung; Sivanantham, Arumugam; Hwang, Sung Won; Surendran, Subramani; Sim, Uk; Cho, In Sun (Ceramics International, 2021)
A key challenge in photoelectrochemical water-splitting is the development of photoanodes with improved chemically active and optically efficient. While various nanostructures in heterogeneous materials have been investigated as a potential electrode, existing structures/compositions are still insufficient to meet such demand. Here, we report a scalable strategy to fabricate photoanodes with a nanotubular structure using CdS–TiO2 heterogeneous composite as a model system. Precisely, a ~5 μm thick nanotubular CdS–TiO2 heterostructure is developed on fluorine-doped tin oxide glass by hydrothermal etching and successive ionic layer deposition process. An electron microscopy analysis confirms that the formation of TiO2 nanotubes in the preferential etching direction of [001] as well as uniform coating of the CdS light-absorber layer. We note that the CdS coated on TiO2 nanotubes shows a photocurrent density of 6.9 mA/cm2 at 1.23 VRHE, which is ~2 times higher than that of CdS- nanorod TiO2 heterostructured photoanode. The elemental and optical analysis reveals that the structural modification and sufficient CdS deposition captures a wide range of light absorption from 300 to 550 nm. Our results suggest that an effective fabrication method is applicable for electrodes in numerous energy conversion devices, providing an increase in surface area, light absorption, and chemical stability.
Keywords: Electron microscopy analysis; Energy conversion devices; Fluorine doped tin oxide; Heterogeneous composites; Photoelectrochemical performance; Photoelectrochemical water splitting; Structural modifications; Successive ionic layer depositions; CdS; Heterostructure; Photoelectrochemistry; Solar water splitting; TiO2; Water oxidation